On an equation related to nonadditive entropies in information theory - Nath, P.; Singh, D. K. (Vysoké učení technické v Brně, Fakulta strojního inženýrství, Ústav matematiky, 2017)
The paper provides the general solutions of a sum form functional equa- tion containing three unknown mappings with some of the solutions related to the nonadditive entropies in information theory
Keywords: functional equation; additive mapping; multiplicative mapping; logarithmic mapping